Feeling of pessimism among widows (Journal of the College of Basic Education, 2023)
The multiple wars that Iraq went through left many political, economic, social and psychological crises during the past three decades, such as the US-British war on Iraq in 2003, as well as the terrorist operations that Iraq witnessed, which left huge numbers of widows (Najm, 2009: 22).Some reports speak of (100) Iraqi women being widowed every day, perhaps more, and that the wife is the one who suffers the greatest affliction, as she lost the breadwinner and the sponsor at the same time and forever. What is remarkable about the matter is that the majority of widows are young women who lose their young husbands as a result of a terrorist bombing, assassination or Killing on identity, and that the records of the Iraqi Ministry of Women’s Affairs say that (95,881) widows who are registered only in the Women’s Care Network are present in Baghdad alone, in addition to (3,238,098) widows in the rest of the provinces of Iraq, which are numbers that can rise daily, and the widow suffers from what she suffers and has to bear the burdens of raising Children and their care (Abd Mohi, Al-Obaidi, 2008: 2).Widowed women are among the groups that are most exposed to stress and traumatic events, because the husband represents the strength upon which the wife relies in the exercise of her life.All this leads to psychological damage that affects the individual, and it is the starting point for many psychological disorders and problems that the widow can suffer and complain about, led by the subjective feeling of unhappiness and the feeling of pessimism as well as the compulsive feeling of helplessness (Al-Nayal, 1993: 4).And when we look closely at our society, we find that our customs and traditions support the sad stimuli, so we find that people deal with weddings with simple ceremonies, but they are almost limited in their duration and the methods of expressing them, so that we find some who fear joy because they believe that joy always comes with many sorrows or something frightening. Upbringing left its mark on behavior and ways of facing life (Jawad, 2005: 3).Where the feeling of pessimism is considered one of the psychological obstacles that impede the individual's ability to control, and exhaust his effectiveness and efficiency in his future life and develop in him negative intellectual and psychological effects and weaken his ability and personal strength in his interaction in his ordinary life, as a result of his pessimistic view, which generates feelings of despair and defeat (Al-Bukhari, 1987: 8). ).The researcher sensed the problem by submitting an exploratory questionnaire that included a question about their feelings of pessimism to a sample of (50) widows, to make sure that there was a problem of feeling pessimistic. (90%) of the sample confirmed that they had a feeling of pessimism, and 10% did not have a feeling of pessimism, which He encouraged the researcher to think about studying this problem on the ground and proposing appropriate solutions to treat it, thus helping them to get out of the state of grief and helplessness.Therefore, the researcher considered a solution to this problem in building a proposed counseling program to reduce the feeling of pessimism among widows.